2010
DOI: 10.1111/j.1740-8261.2010.01700.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Magnetic Resonance Volumetry of the Hippocampus in 58 Epileptic Dogs*

Abstract: Hippocampal atrophy, which is a component of hippocampal sclerosis and recognized commonly in human intractable epilepsy, is controversial in canine epilepsy. We examined the hippocampal volume in 58 epileptic dogs and 35 control dogs using magnetic resonance (MR) images, and calculated the relative hippocampal volume asymmetry of the right and left hippocampus. Subjectively, there were visible MR imaging abnormalities in seven of the 58 epileptic dogs (12%). The hippocampel volume asymmetric ratio of epilepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
50
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 31 publications
(48 reference statements)
5
50
0
1
Order By: Relevance
“…To our knowledge, no study about T2 relaxometry of the hippocampus in epileptic companion animals has yet been published in veterinary medicine, although the hippocampus may play an important role in canine and feline epileptogenesis and seizure semiology, in similar way as in human patients (Kuwabara et al, 2010;Pákozdy et al, 2011). An experimental rat model of hippocampal sclerosis provided the same results as seen in human studies (Parekh et al, 2010), but due to its experimental nature, it is not quite as conclusive in the veterinary practice.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…To our knowledge, no study about T2 relaxometry of the hippocampus in epileptic companion animals has yet been published in veterinary medicine, although the hippocampus may play an important role in canine and feline epileptogenesis and seizure semiology, in similar way as in human patients (Kuwabara et al, 2010;Pákozdy et al, 2011). An experimental rat model of hippocampal sclerosis provided the same results as seen in human studies (Parekh et al, 2010), but due to its experimental nature, it is not quite as conclusive in the veterinary practice.…”
supporting
confidence: 63%
“…In a volumetric study involving 58 epileptic dogs, the authors found a significantly greater hippocampal volumetric asymmetry ratio in epileptic dogs than in the control group, which is suitable for detecting unilateral, but not bilateral changes (Kuwabara et al, 2010). According to human studies, hippocampal relaxometry is more sensitive than volumetry to determine hippocampal atrophy, and it can also detect bilateral abnormalities (Grünewald et al, 1994;Bernasconi et al, 2000;Okujava et al, 2002;Scott et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual differences in brain structure as assessed by different imaging modalities, such as cortical thickness, or diffusion tensor imaging [54], may be related to normal variations of behavior or one of many disease states. Indeed, the canine is a valuable model system for many neurological diseases, including epilepsy [55]; cortical malformations such as lissencephaly [56], [57] and polymicrogyria [58], [59]; dementia [60], [61]; and focal lesions [62], [63]. Given the good registration of high-resolution anatomy with a head model, the atlas can be used to guide source localization of EEG recording in the dog [64].…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of large animal models of temporal lobe epilepsy. In dogs, for example, spontaneous epi-lepsy is common (Potschka et al, 2013), but temporal lobe epilepsy is rare (Buckmaster et al, 2002b;Kuwabara et al, 2010). Non-human primate models of temporal lobe epilepsy have been developed (Ribak et al, 1998;Gunderson et al, 1999) or attempted (Perez-Mendes, 2005), but they involve ethical questions and practical limitations.…”
mentioning
confidence: 99%